Lithium increases 5-HT-mediated neuroendocrine responses in tricyclic resistant depression. - Cowen, P; McCance, S; Cohen, P; Julier, D (1989)
The addition of lithium to the tricyclic antidepressant medication of 11 depressed patients resulted in an increase in the prolactin response to L-tryptophan after both 4 days and 4 weeks of lithium treatment. There was also a significant fall in Hamilton Depression scores. The results suggest that lithium and tricyclic antidepressants may act synergistically to enhance certain aspects of brain 5-HT function in depressed patients.